2010
DOI: 10.1016/j.ultrasmedbio.2010.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Inertial Cavitation Threshold and Skull Effects in a Vessel Phantom Using Focused Ultrasound and Microbubbles

Abstract: Focused ultrasound (FUS) in combination with microbubbles has been shown capable of delivering large molecules to the brain parenchyma through opening of the blood-brain barrier (BBB). However, the mechanism behind the opening remains unknown. To investigate the pressure threshold for inertial cavitation of preformed microbubbles during sonication, passive cavitation detection in conjunction with B-mode imaging was used. A cerebral vessel was simulated by generating a cylindrical hole of 610 µm in diameter ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 32 publications
5
72
0
Order By: Relevance
“…Both stable and inertial cavitation have been observed to both mechanically agitate the microvascular wall (8) and cause extravasation of vascular agents (7,21). Previous reports using longer PLs of 10 or 20 ms have analyzed the acoustic emissions radiating from the acoustically driven microbubbles and have indicated that BBB disruption may occur with stable cavitation or nonviolent inertial cavitation (22)(23). However, it is difficult to infer to the type of cavitation activity present in our experiments due to the shorter duration of the PL used and the fact that we are operating at PRPs near the threshold of BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Both stable and inertial cavitation have been observed to both mechanically agitate the microvascular wall (8) and cause extravasation of vascular agents (7,21). Previous reports using longer PLs of 10 or 20 ms have analyzed the acoustic emissions radiating from the acoustically driven microbubbles and have indicated that BBB disruption may occur with stable cavitation or nonviolent inertial cavitation (22)(23). However, it is difficult to infer to the type of cavitation activity present in our experiments due to the shorter duration of the PL used and the fact that we are operating at PRPs near the threshold of BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…McDannold et al (24) proposed the potential of using microbubble emissions to control the BBBD, based on a correlation found between the strength of second/ third harmonic components and MRI contrast enhancement post BBBD. This potential has been further suggested by several BBBD works with cavitation monitoring (21,(25)(26)(27) and other microbubble-mediated therapies (28,29). O'Reilly and Hynynen (30) designed an active controller that increases the acoustic pressure until ultraharmonic emission is detected and then reduces it by a predetermined amount.…”
mentioning
confidence: 99%
“…However, this controller becomes openloop after ultraharmonics are detected, leaving the rest of the sonication uncontrolled. Moreover, its performance relies on the detection of ultraharmonics, which may be challenging in the presence of the skull (25), in the varying ambient pressure (31), or in the case of a high broadband noise level. Having a method to further control the exposure level would be desirable and could enhance confidence that an appropriate exposure level is maintained.…”
mentioning
confidence: 99%
“…Nonetheless, cavitation is a very complicated process that not only depends on the pressure but also on the amount of dissolved gas and other properties of the fluid or tissue. Moreover, cavitation thresholds in the brain are variable and still largely unknown [101,61,100,62]. In this paper, we are only concerned with the possibility of cavitation in the saline solution in the transwell, which was not de-gassed in the experiment reported here.…”
mentioning
confidence: 99%